Decolonizing First Nations Health and Social Services Funding in Canada - Spotton Visano, Brenda; McBroom, Susan; Vanloffeld, Steven; Wheeler, Glenn (The International Indigenous Policy Journal, 2025)
This article considers the many ways in which mechanisms delivering funding for health and social services to First Nations on reserve embed colonial biases. Against a backdrop of trade-offs inherent in different funding mechanisms, we examine the extent to which colonial biases result in greater need for health and social services for which the same per unit funding would be inadequate, and how the colonial biases in operationalizing the funding mechanisms result in lower per unit funding than is afforded Canadians, in some instances. For better informing current efforts to co-develop a renewed fiscal federalism, we conclude with a path forward cast as different decolonizing options of increasing complexity.